2012
DOI: 10.1038/modpathol.2011.143
|View full text |Cite
|
Sign up to set email alerts
|

Accumulative copy number increase of MET drives tumor development and histological progression in a subset of ovarian clear-cell adenocarcinomas

Abstract: Our previous study demonstrated that, among ovarian carcinomas, amplification of the MET gene and overexpression of MET specifically and commonly occur in clear-cell adenocarcinoma histology. This study was conducted to address how these alterations contribute to development and progression of this highly chemoresistant form of ovarian cancer. We histologically reviewed 21 previously described MET amplificationpositive clear-cell adenocarcinoma cases, and selected 11 tumors with synchronous endometriosis and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 38 publications
2
26
1
Order By: Relevance
“…As we observed in mutation profiles, our bona-fide CCC cell line panel was representative of clear-cell associated copy number changes (Figure 2, Table 3). Most showed modest copy number gains for HNF1B (5/7) and MET (4/7) , including one with high-level amplification (JHOC-5), similar to previous reports for CCC tumors [53], [56], [57]. Although 3/7 CCC lines showed copy number gain of ERBB2 , in all cases the amplicon segment also encompassed the nearby CCC biomarker HNF1B , and none were positive for HER2 protein expression by IHC (not shown).…”
Section: Resultssupporting
confidence: 88%
“…As we observed in mutation profiles, our bona-fide CCC cell line panel was representative of clear-cell associated copy number changes (Figure 2, Table 3). Most showed modest copy number gains for HNF1B (5/7) and MET (4/7) , including one with high-level amplification (JHOC-5), similar to previous reports for CCC tumors [53], [56], [57]. Although 3/7 CCC lines showed copy number gain of ERBB2 , in all cases the amplicon segment also encompassed the nearby CCC biomarker HNF1B , and none were positive for HER2 protein expression by IHC (not shown).…”
Section: Resultssupporting
confidence: 88%
“…We observed DNA copy number gains in a number of previously documented CCC‐associated genes, including regions of 17q: HNF1B (5/7), PPM1D (5/7), ERBB2 (4/7), STAT3 (4/7); 3q PIK3CA (4/7); 7q: MET (2/7) and 20q: ZNF217 (6/7), including one high‐level gain of PIK3CA observed in case 7. Despite other reports showing common amplification of MET in CCC , we did not observe any such events in our cohort, neither did we observe classic high‐level amplification of ERBB2 , as has been previously reported in breast and mucinous ovarian cancer .…”
Section: Resultscontrasting
confidence: 81%
“…Previous studies have identified shared patterns of LOH [10,11] as well as single gene abnormalities [13,15] clonally linking endometriosis adjacent to CCC and ENOCa. We extend these observations, demonstrating that some endometriosis lesions have an extensive subset of the mutations present in the associated CCC, and have thus progressed further towards cancer than was previously appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…However, PIK3CA mutations are more frequent in OCCA (>40%) than in OSA (<10%) [17]. Although mutations of KRAS and PTEN are rare (<10%), the overexpression of several RTKs has been reported in OCCA, including human epidermal growth factor receptor 2 (HER2) with a frequency of approximately 40% and cMET with a frequency of approximately 30% [18][21]. Taken together, these observations suggest that the RTK-PI3K/mTOR signaling axis might be broadly activated in OCCA.…”
Section: Introductionmentioning
confidence: 99%